PENINGKATAN HASIL BELAJAR IPS MENGGUNAKAN METODE DISKUSI DI KELAS V SDN 05 TEMU TERIAK - Aco, Herkulanus; Asran, Marzuki; Asran, Mastar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to improve student learning outcomes in the learning of Social Sciences by using the discussion method in class V of Elementary School 05 Temu Bengkayang Regency. The research method used is descriptive, a form of classroom action research research. Data collection techniques used are direct observation and document scrutiny. Data collection tools used are observation sheets and student learning outcomes documents. This research was carried out in three cycles, the results obtained were (1) the ability of the teacher in compiling the plan for the implementation of learning in the first cycle which was 2.41 with enough categories, in the second cycle was 3 with good categories and the last in the third cycle was 3.83 with very good category. (2) The ability of the teacher to carry out in the first cycle is 2.41 with enough categories, in the second wide 3.28 with good categories and in the third cycle 3.76 with very good categories. (3) The application of discussion learning methods can increase the average learning outcomes, namely in the first cycle of 69.47 and, the second cycle of 80 and the third at 95.78. The conclusion in this study is that there is an increase in student learning outcomes by using a discussion method in learning social science in class V of Public Elementary School 05 Temu Bengkayang.  Keywords: Discussion Method, Learning Outcomes, Social Sciences.